1976
DOI: 10.1111/j.1540-4560.1976.tb02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Breakups Before Marriage: The End of 103 Affairs

Abstract: Factors that predicted breakups before marriage, investigated as part of a two-year study of dating relationships among college students, included unequal involvement in the relationship (as suggested by exchange theory) and discrepant age, educational aspirations, intelligence, and physical attractiveness (as suggested by filtering models). T h e timing of breakups was highly related to the school calendar, pointing to the importance of external factors in structuring breakups. T h e desire to break up was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
289
7
6

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(324 citation statements)
references
References 11 publications
22
289
7
6
Order By: Relevance
“…Sprecher (1994) found no significant difference between men's and women's experienced distress after a relationship breakup. This was in contrast to Hill, Rubin, and Peplau's (1976) study of 103 breakups, in which they found men experienced more depression, loneliness, and guilt after disengagement. Helgeson (1994) studied long distance relationship dissolution, and found that men experienced more distress when the breakup occurred, which was especially acute in men who did not initiate the breakup.…”
Section: Relationship Dissolutioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Sprecher (1994) found no significant difference between men's and women's experienced distress after a relationship breakup. This was in contrast to Hill, Rubin, and Peplau's (1976) study of 103 breakups, in which they found men experienced more depression, loneliness, and guilt after disengagement. Helgeson (1994) studied long distance relationship dissolution, and found that men experienced more distress when the breakup occurred, which was especially acute in men who did not initiate the breakup.…”
Section: Relationship Dissolutioncontrasting
confidence: 99%
“…Some studies found women experience more distress in general, while others found no differences (Hill, et al, 1976;Sprecher, 1994). In addition to an examination of gender differences in distress, the present study explored the possibility of gender moderating the relationship between the coping variables and distress after dissolution.…”
Section: Hypothesis IVmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to the poor relationship quality experienced by those high on Machiavellianism, we predicted lower post break up distress for those with high levels of Machiavellianism. Important sex differences occur with regard to relationship dissolution; for example women are more likely than men to initiate a break up (Hill, Rubin, & Peplau, 1976), cite different reasons for break ups (Lampard, 2014), and adjust better to relationship dissolution (Evans, Scourfield, & Moore, 2014;Helgeson, 1994). Furthermore, it has been argued that the influence of Machiavellianism on interpersonal relationships may differ for men and women (McHoskey, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In most Western societies, men and women follow a pattern of serial monogamy characterised by the repeated formation and dissolution of romantic relationships (Fisher, 1985;MacDonal, 1995). When relationships are terminated (i.e., a 'break up'), it is typically instigated by one member of the couple, with mutual agreement less prevalent (Hill, Rubin, & Peplau, 1976). Factors increasing the likelihood of relationship dissolution include a partner's failure to meet 2 expectations (e.g., sexual dissatisfaction), unequal commitment, a desire for freedom, and external factors (Connolly & McIsaac, 2009;Hill, Rubin, & Peplau, 1976;Sprecher, 1994).…”
Section: Introductionmentioning
confidence: 99%